Performance Evaluation of Using Artificial Intelligence Technology in Cashless Payment Systems - Alexey V. Bataev (Communications of International Proceedings, 2021)
The possible prospects for using artificial intelligence in the financial sphere are analyzed in this study. One of the possible areas of using neural network in financial institutions is the system of cashless payments. One of the main problems in introducing innovative projects is to evaluate the efficiency of the implemented information system. In connection with this, the construction of an investment model that allows evaluating the implementation and use of artificial intelligence in the cashless payments system of financial institutions is proposed in this article. Based on the constructed model, an analysis is made of the dependence of the effectiveness of the system with artificial intelligence on the size of the client base of a credit organization, while the minimum and maximum possible efficiency parameters of the implemented system are evaluated. Based on a comprehensive analysis, recommendations are given on the prospects of introducing such systems into credit organizations.
Keywords: Information Technology Management; Digital Economy; Innovation; Neural Network Technologies; Financial Institutions; Cashless Payments; Modeling; Efficiency